Collision modeling and two-echelon collaborative control of non-contact ultra-quiet Stewart spacecraft - He Liao; Xiande Wu; Yufei Xu; Xinzhu Sun; Zhipeng Wang (Advances in Mechanical Engineering, 2018)
This article presents the collision modeling and two-echelon collaborative control of a novel non-contact ultra-quiet Stewart spacecraft. It has internal instability because of its non-contact configuration. To overcome the instability, the equivalent modeling of repetitive collision process with small releasing velocity is established at first. Then, a two-echelon collaborative control is developed to guarantee both collision rejection and stability performance. Finally, the numerical simulation is conducted to demonstrate the validity and effectiveness of the proposed design.